A Review of Green Supply Chain Management Practices in Asian Countries - Irum, Sobia; Imran Qureshi, Muhammad; Ashfaq, Muhammad; Sami, Abdul; N. Bhatti, Mansoor; Umar, Arslan (International Journal of Engineering and Technology, 2018)
This paper offers a systematic review of 22 research articles published on the green supply chain management practices in developing Asian countries between 2008 to 2017. With the increasing trend in the depletion of environmental resources, the green supply chain management practices are considered prudent. Their impact on firmâ€™s performance has been well established. Review of articles revealed that interest in the topic of green supply chain management practices has grown significantly during the last decade, and will remain a fertile area for academic research in the years to come. Findings revealed that the green supply chain management practices lead to enhanced performance in four areas: economic, environmental, operational, and social.Â Â